Implementasi dan Analisis Gamifikasi pada Aplikasi Manajer Keuangan Pribadi - Rina Yulius; Muchamad Fajri Amirul Nasrullah (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2019)
This study aimed to design a gamification-based personal financial application and investigate the relationship between self-determination motives and user engagement. Data of 152 participants were collected through online questionnaire. The participants consisted of users who have Android-based smartphone and use the personal financial application, EasySaku, at the same time. Simple linear regression analysis and multiple linear regression analysis were used to test the hypotheses. The results show that there is a significant relationship between self-determination motives and user engagement. The relationship is partially mediated with gamified app, EasySaku.